2020
DOI: 10.1002/1873-3468.13873
|View full text |Cite
|
Sign up to set email alerts
|

The β‐turn‐supporting motif in the polyglutamine binding peptide QBP1 is essential for inhibiting huntingtin aggregation

Abstract: Aggregation of polyglutamine proteins is a hallmark of several neurodegenerative diseases. The 11‐residue polyglutamine binding peptide Ac‐SNWKWWPGIFD‐am, known as QBP1, inhibits polyglutamine aggregation. Besides, a minimal 8‐residue stretch in the QBP1 peptide (Ac‐WKWWPGIF‐am) is reported in the literature to retain this activity. Both peptides harbor a Pro‐Gly dipeptide motif, a feature characteristic of potential β‐turn regions. Here, we investigated whether the presence of this β‐turn motif is necessary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…By incorporating this structural feature, QBP1 and mQBP1 can exert their inhibitory effects on HDx1 aggregation. 112 In specific cases, it has been observed that QBP1 and mQBP1 can retain their inhibitory activity even when the PG motif is replaced with other β-turn supporting residues. For example, variants such as QBP1-pG, QBP1-UG, and QBP1-NG, where the PG motif is substituted with alternative residues that support β-turn conformation, maintain their activity in inhibiting Trx-HDx1 aggregation.…”
Section: Pro-gly Mutant Peptides Of Polyqmentioning
confidence: 99%
See 2 more Smart Citations
“…By incorporating this structural feature, QBP1 and mQBP1 can exert their inhibitory effects on HDx1 aggregation. 112 In specific cases, it has been observed that QBP1 and mQBP1 can retain their inhibitory activity even when the PG motif is replaced with other β-turn supporting residues. For example, variants such as QBP1-pG, QBP1-UG, and QBP1-NG, where the PG motif is substituted with alternative residues that support β-turn conformation, maintain their activity in inhibiting Trx-HDx1 aggregation.…”
Section: Pro-gly Mutant Peptides Of Polyqmentioning
confidence: 99%
“…The inability of QBP1-PP to inhibit aggregation further highlights the importance of the specific structural elements and residues in QBP1 and mQBP1 for their functional effectiveness in preventing protein aggregation (Figure 10). 112 There are three methods for delivering QBP1 to the affected neurons in the brain (Figures 11, 12, and 13):…”
Section: Pro-gly Mutant Peptides Of Polyqmentioning
confidence: 99%
See 1 more Smart Citation
“…The p42 binds on 480 residues to 502 residues while QBP 1 binds on other sites in N terminal region of Htt protein. Herein, we have compared peptide-based (ED 11, Exendin-4, CaM, QBP1, BIP) therapeutic approach for targeting the aggregate prone areas in Htt protein, that can decelerate the progression of disease [ 12 , 13 , 14 ]. QBP1 and p42 targets poly Q disease, ED11 targets caspase 6 but is used in Huntington's therapy.…”
Section: Introductionmentioning
confidence: 99%